The Influence of Education Level, Unemployment Rate, and Health Level on Economic Growth and Poverty Rate in Indonesia from 2010 to 2023 - Faizal Adi Bahtia, Jeri; Munawar, Munawar; Kresna Sakti, Rachmad (Jurnal Indonesia Sosial Sains, 2025)
This study analyzes the effects of education level, unemployment rate, and health level on economic growth and poverty rates in Indonesia during the 2010–2023 period. Panel data from 33 provinces sourced from the Central Bureau of Statistics (BPS) were utilized. Education level was measured by average years of schooling, unemployment by the open unemployment rate, and health by life expectancy. Economic growth was assessed using Gross Regional Domestic Product (GRDP), and poverty was measured by the poverty line. Multiple linear regression analysis with two models was employed to examine direct and mediating effects. The results indicate that education and health levels have significant negative effects on poverty and a positive effect of education on economic growth. The unemployment rate showed no significant impact on either poverty or economic growth. Economic growth was not found to significantly mediate the relationship between independent variables and poverty. These findings provide important insights into the factors influencing poverty and economic growth in Indonesia, emphasizing the role of human capital development in regional economic policies.